Mesodiplatys venado sp. nov. (Dermaptera: Diplatyidae), probable evidence of contact between Neotropical and Malagasy faunas - Anisyutkin, Leonid N. (Zootaxa, 2014)
A new earwig of the Malagasy genus Mesodiplatys stat. nov., M. venado sp. nov. (Dermaptera: Diplatyidae) is described from Peru (Departament Junin, Satipo Province). The diagnosis and composition of the genus Mesodiplatys stat. nov. are discussed. A detailed morphological description of the new species is given. The possible biogeographical significance of the find as evidence of link between South American and Malagasy fauna is briefly considered.